Tourism application -TOUCH / Siti Hafizah Dzulkarnain ... [et al.] - Dzulkarnain, Siti Hafizah; Mustaffa Ma'arof, Amira Naqiyyah; Hamzah, Nursyahidah; Mohammad Hazlan, Nur Hidayah; Sun Fatt, Boyd (2021)
Sustainable tourism has become a major focus in the tourism industry. This product can help and improve the tourism industry by the consumer making better purchase decisions and the wholesalers can maximise marketing and operations. The objective of this travel application is to educate, improve user experience and manage booking in a systematic environment. This application combines booking and socializing into one application. The newly designed prototype is a showcase of attractions in Malaysia that help travellers to find interesting places to visit, learn more about it and make bookings to the attractions, extending the booking to other service-related activities such as accommodation, transportation and food and beverage. Users can utilise the application and take the experience to the next level where they can connect, converse and discuss with others on the place of interest, as well as view feedback and ratings. This application aims to ease the process of a trip before, during and after. This platform will also showcase for wholesalers to provide their package under the selection of an attraction to ease the users in finding the perfect package for their holiday.